Fixed Points and Stability of a Generalized Quadratic Functional Equation. (24th February 2009) - Najati, Abbas; Park, Choonkil
Abstract : Using the fixed point method, we prove the generalized Hyers-Ulam stability of the generalized quadratic functional equationf ( r x + s y ) = r 2 f ( x ) + s 2 f ( y ) + ( r s / 2 ) [ f ( x + y ) − f ( x − y ) ] in Banach modules, wherer, s are nonzero rational numbers withr 2 + s 2 ≠ 1 .